Descriptive Epidemiology of Cervical Dystonia. (4th November 2013) - Defazio, Giovanni; Jankovic, Joseph; Giel, Jennifer L.; Papapetropoulos, Spyridon
Background: Cervical dystonia (CD), the most common form of adult-onset focal dystonia, has a heterogeneous clinical presentation with variable clinical features, leading to difficulties and delays in diagnosis. Owing to the lack of reviews specifically focusing on the frequency of primary CD in the general population, we performed a systematic literature search to examine its prevalence/incidence and analyze methodological differences among studies. Methods: We performed a systematic literature search to examine the prevalence data of primary focal CD. Sixteen articles met our methodological criteria. Because the reported prevalence estimates were found to vary widely across studies, we analyzed methodological differences and other factors to determine whether true differences exist in prevalence rates among geographic areas (and by gender and age distributions), as well as to facilitate recommendations for future studies. Results: Prevalence estimates ranged from 20–4, 100 cases/million. Generally, studies that relied on service-based and record-linkage system data likely underestimated the prevalence of CD, whereas population-based studies suffered from over-ascertainment. The more methodologically robust studies yielded a range of estimates of 28–183 cases/million. Despite the varying prevalence estimates, an approximate 2:1 female:male ratio was consistent among many studies. Three studies estimated incidence, ranging from 8–12 cases/million person-years. Discussion: Although several studies have attempted to estimate the prevalence and incidence of CD, there is a need for additional well-designed epidemiological studies on primary CD that include large populations; use defined CD diagnostic criteria; and stratify for factors such as age, gender, and ethnicity.